ANALYSIS OF FLOOD DISASTER AREAS, JOMBANG REGENCY, EAST JAVA USING ARCGIS REMOTE SENSING - Iswandaru, Yoga Satria Iswandaru; Widodo, Amien; Singgih Purwanto , Moh. (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2021)
Flood is one of the natural disasters that occur in Indonesia. Each region in Indonesia has a different flood hazard level. Therefore, a study was conducted to map the level of flood hazard in Jombang Regency, East Java. Remote sensing methods are used to map flood-prone areas, ArcMap software is used to map disaster-prone areas and mapping vegetation density. The data required is in the form of flood data index from Inarisk and Landsat 8 imagery data from USGS. From these data, four maps were generated, namely the vegetation density map and the flood hazard map in the Jombang area. From the vegetation density map, it can be seen from the value it determines the level of vegetation density in the area, while the flood hazard map is categorized into three hazard categories, namely low, medium and high. And it was found that the lower the level of vegetation density, the higher the level of flood hazard in the area, and vice versa and it is also known that the Brantas river affects flooding in Jombang. Then seen from the regional geology, the area of North Jombang absorbs air more quickly because it is composed of karst rocks. Judging from the area of the flood hazard level, the Jombang area is more dominant to the moderate hazard level.